2022
DOI: 10.3389/fmed.2022.813343
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Roles of Uterine Artery Doppler in Pregnancy Complications

Abstract: The invasion of trophoblasts into the uterine decidua and decidual vessels is critical for the formation of placenta. The defects of placentation are related to the etiologies of preeclampsia (PE), fetal growth restriction (FGR), and small-for-gestational age (SGA) neonates. It is possible to predict significant vascular events during pregnancy through uterine artery Doppler (UAD). From the implantation stage to the end of pregnancy, detecting changes in uterine and placental blood vessels can provide a favora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 149 publications
(240 reference statements)
0
13
0
Order By: Relevance
“…Te kinetic parameters will decrease accordingly. Studies have shown that uterine artery hemodynamic parameters in patients with preeclampsia are signifcantly higher than those in normal pregnant women [19]. Ultrasound technology enables the noninvasive and real-time assessment of hemodynamic parameters in vital organs of pregnant women and fetuses [20].…”
Section: Introductionmentioning
confidence: 99%
“…Te kinetic parameters will decrease accordingly. Studies have shown that uterine artery hemodynamic parameters in patients with preeclampsia are signifcantly higher than those in normal pregnant women [19]. Ultrasound technology enables the noninvasive and real-time assessment of hemodynamic parameters in vital organs of pregnant women and fetuses [20].…”
Section: Introductionmentioning
confidence: 99%
“…PE can be predicted with more accuracy in the second trimester of conception by the use of Uterine Artery Doppler study than in the first, according to research on the subject. It also played a significant part in foretelling severe or early-onset PE in lowrisk populations [30] . Doppler studies of the uterine artery may be more predictive of PE if measured repeatedly in the first half of conception, according to research, which also found that using the firsttrimester uterine artery Doppler in PE anticipation had an overall sensitivity of 26% and specificity of 91%.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have indicated that it is possible to predict significant vascular events during pregnancy through uterine artery Doppler examination. [27] High maternal BMI might decrease the uterine artery pulsatility index (UtA-PI). [28] The UtA-PI of the placental side is lower than that of the non-placental side.…”
Section: Discussionmentioning
confidence: 99%